Trends of nanotechnology in type 2 diabetes mellitus treatment - Yannis V. Simos; Konstantinos Spyrou; Michaela Patila; Niki Karouta; Haralambos Stamatis; Dimitrios Gournis; Evangelia Dounousi; Dimitrios Peschos (Elsevier, 2021)
There are several therapeutic approaches in type 2 diabetes mellitus (T2DM). When diet and exercise fail to control hyperglycemia, patients are forced to start therapy with antidiabetic agents. However, these drugs present several drawbacks that can affect the course of treatment. The major disadvantages of current oral modalities for the treatment of T2DM are mainly depicted in the low bioavailability and the immediate release of the drug, generating the need for an increase in frequency of dosing. In conjugation with the manifestation of adverse side effects, patient compliance to therapy is reduced. Over the past few years nanotechnology has found fertile ground in the development of novel delivery modalities that can potentially enhance anti-diabetic regimes efficacy. All efforts have been targeted towards two main vital steps: (a) to protect the drug by encapsulating it into a nano-carrier system and (b) efficiently release the drug in a gradual as well as controllable manner. However, only a limited number of studies published in the literature used in vivo techniques in order to support findings. Here we discuss the current disadvantages of modern T2DM marketed drugs, and the nanotechnology advances supported by in vivo in mouse/rat models of glucose homeostasis. The generation of drug nanocarriers may increase bioavailability, prolong release and therefore reduce dosing and thus, improve patient compliance. This novel approach might substantially improve quality of life for diabetics. Application of metal nanoformulations as indirect hypoglycemic agents is also discussed.